IPHONE DALAM PERSPEKTIF NILAI TANDA DAN SIMBOL DI KALANGAN MAHASISWA FISIP UNSRI - Sari, Rama Dian; Sartika, Diana Dewi; Soraida, Safira; Istiqoma, Istiqoma (Sociology Department Of Syiah Kuala University, 2023)
This article aims to describe the differences in the value of objectswhichhave the same function butithasdifferent symbols and signs. In this case, the value of signs and symbols on Apple products, namely the iPhone, generally has the same function as other smartphone products.The purpose of this study was to understand the value of the Appleproduct (iPhone) for Indralaya Faculty of Social and Political Sciences students atSriwijaya University. The method used in this research is qualitativewithacase study approach. Datacollection techniques were carried out through interviews, observation, anddocumentation methods. The result of this research is that the iPhone is not only asmartphone that is used to communicate, but more than that, it is also used as apersonality. There are various kinds of economic backgrounds among iPhone userstudents, namely the lower-class economy, the middle-class economy, and theupper-class economy. iPhone user students feel that there is a difference whenusing the iPhone, such as growing self-confidence and pride and being able tosupport students; social status. The value of signs and symbols is abstract andconstructed as a whole. The sign value on the iPhone relates to the concept ofluxury, while the symbol value consists of symbols such as upper class, elegance,lifestyle, and youth.